Pengaruh Program Makan Siang terhadap Asupan Makanan, Status Anemia dan Perilaku Gizi Santri Perempuan - Kusumawati, Dewi; Rimbawan, Rimbawan; Ekayanti, Ikue (Media Kesehatan Masyarakat Indonesia, 2019)
Provision of food in dormitories is generally limited due to cost problems so students are vulnerable to malnutrition. Iron deficiency in adolescents can cause anemia. This study aimed to evaluate effect of lunch program on food intake, anemia status and nutritional behaviour for female students at the Darusalam Islamic Boarding School Bogor. This study was a pre-experiment with one group design before intervention. Selected subjects were 54 students given interventions of adding protein and fruit at lunch and nutrition education for 15 weeks. Nutrition education delivered by the teacher and refreshment material by nutrition students. The results showed energy, protein, fat, carbohydrate, fiber, calcium, zinc, iron and Vitamin C increased in lunch intake and differed significantly from before intervention (p<0.05). Nutritional status (BMI/U) increased and differed significantly before and after the intervention (p<0.05). The proportion of anemia status increased to be better and significantly higher than the comparison but increased hemoglobin levels of 0.14±1.12 g/dl have not been able to provide a significant average hemoglobin level (p>0.05). Knowledge and nutritional attitudes of students about anemia were significantly different between before and after intervention (p<0.05).